Estimate and reporting of longevity for cardiac implantable electronic devices: a proposal for standardized criteria. (2nd December 2021) - Censi, Federica; Calcagnini, Giovanni; Mattei, Eugenio; Ricci, Renato Pietro; Zoni Berisso, Massimo; Landolina, Maurizio; Boriani, Giuseppe
ABSTRACT: Background: Cardiac implantable electronic devices (CIEDs) are widely used according to consensus guidelines in various patient categories. The longevity of CIED is a major determinant of the frequency with which patients require device replacement. Given the mismatch between the useful life of the devices and patient survival, device replacement is often needed. There is a great variability in the criteria used by manufacturers to determine the longevity of pacemakers (PM), implantable defibrillators (ICDs), and devices for cardiac resynchronization therapy (CRT). Thus, a fair comparison and an effective device evaluation is often difficult. Methods: The objective of this paper is to provide standardized criteria based on typical clinical settings for estimating the longevity of single and dual chamber ICDs, cardiac resynchronization defibrillators (CRT-D), single and dual chamber PMs, and cardiac resynchronization PMs (CRT- P) to be used in health technology assessment for an appropriate comparison among different devices. Results: The proposed parameters, if applied to the current marketed devices, provide longevity values in the range 5–17.2 years. Conclusion: The values of longevity with the non-standardized criteria used by the manufacturers result in higher maximum values respect to the proposed standardized criteria for CRT-D, CRTD-MPP, CRT-P, and Dual-chamber PM.